KERAGAAN DUA VARIETAS JAGUNG MANIS DENGAN PEMBERIAN POC LIMBAH INDUSTRI IKAN ASIN DILAHAN RAWA LEBAK - Sarifudin Sarifudin; Jamilah Jamilah; Ahmad Junaidi; Nurul Istiqomah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Most of the results from fisheries in the District of Lake Panggang are processed into salted fish. The processing of fishery products leaves liquid waste. The productivity of maize in this sub-district is also low due to the use of local varieties and without fertilization. Liquid waste processing fishery products can be used as liquid organic fertilizer. Lebak swamp land is land with low nutrient elements. The aims of this study were (i) to determine the interaction of two varieties with POC of salted fish industrial wastewater on the growth and yield of sweet corn in Lebak swamp land, (ii) the effect of two varieties, (iii) the effect of POC of salted fish industrial wastewater, (iv) ) the best interaction of two varieties with POC of salted fish industrial wastewater, (v) knowing the best variety, (vi) best dose of POC of fish industrial wastewater. This research was conducted in Danau Panggang Village, Danau Panggang Sub district, Hulu Sungai Utara Regency from May to August 2021. Using a 2-factor factorial randomized block design (RAK). The first factor is the POC dose of salted fish liquid waste as much as 4 levels, namely i1=30 ml/l, i2=45 ml/l, i3=60 ml/l, i4=75 ml/l. The second factor is two varieties of sweet corn, v1 = Bonanza F1 and v2 = Pertiwi F1. The results showed that the interaction of two varieties with POC of salted fish industrial wastewater affected the number of leaves aged 28 and 35 DAP, but had no effect on the number of leaves aged 14 and 21 DAP and other variables such as plant height, stem diameter, age of first flowering, cob length. Belabor and not belabor and cob weight belabor and not belabor.